ANALISIS YURIDIS PELANGGARAN HAK CIPTA PADA PERBUATAN MEMFOTOKOPI BUKU ILMU PENGETAHUAN - Gede Sastrawan (Ganesha Law Review, 2021)
This article discusses the Juridical Analysis of Copyright Infirigement On The Act Of Photocopying Books of Science. Copyright is a part of Intellectual Property Rights (HKI). The copyright phrase comes from a foreign term, namely Copyrights. The term Copyrights was first put forward in the Berne Comvertion (International Convention on Copyright concerning the protection of Art and Literature) which was held in 1886. According to Article 1 number (1) of Law Number 28 of 2014 concerning Copyright, it states that "Copyright is the right exclusive to the creator that arises automatically based on the declarative principle after a work is manifested in a tangible form without reducing restrictions in accordance with the provisions of the legislation.